234 Effectiveness of Fetal Perflurocarbon Therapy for Lung Hypoplasia in Diaphragmatic Hernia. (October 2012) - Herber-Jonat, S; Vuckovic, A; Mittal, R; Jani, J; Flemmer, AW
Abstract : Aims: To assess the effects of fetal, intratracheal perfluoroctylbromid (PFOB) instillation on lung-mechanics and gene expression of Surfactant and developmental proteins in a newborn rabbit model of lung hypoplasia. Methods: On day 23/31, diaphragmatic hernia was induced by fetal surgery in two fetuses/doe. On day 28/31, the fetuses were randomly instilled with intratracheal PFOB (CDH-PFOB) or saline (CDH-saline). After term delivery, the fetuses were ventilated (30min) and lung-mechanics were measured. Lung-to-body-weight-ratio (LBWR) and mRNA levels of different proteins were determined. Non-operated littermates served as controls. Gene expression was expressed as fold-induction relative to controls. Results: LBWR showed an increase in CDH-PFOB as compared to CDH-saline (p=0.05). Total lung capacity (TLC), static lung compliance (Cst), and RTq-PCR are shown below (+p<0.05 as compared to control, *p<0.05 as compared to CDH-saline): Conclusions: In contrast to previous data addressing tracheal occlusion, PFOB improved TLC and Cst. PFOB also resulted in normalization of Surfactantproteins without inducing extracellularmatrix proteins. Thus, PFOB instillation appears to be a promising therapy for use in fetal lung hypoplasia.